2018
DOI: 10.1080/01480545.2018.1455204
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of chlormethiazole on the toxicokinetics of diethylnitrosamine in normal and hepatofibrotic rats

Abstract: The effect of chlormethiazole (CMZ) at single and multiple doses on the toxicokinetics of diethylnitrosamine (DEN) was investigated in normal rats and those with DEN-induced liver fibrosis. Twelve rats were treated with DEN (50 mg/kg) alone and in combination with a single dose of CMZ (10, 50, or 100 mg/kg) by intraperitoneal (i.p.) injection. In a multiple dose test, six rats were treated with CMZ (50 mg/kg) for 7 d with addition of DEN (50 mg/kg) on days 1 and 7. Lastly, 12 rats were treated with DEN (50 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…This affects the activities of CYPs including CYP2E1, and the important role of CYP2E1 in the activation of procarcinogens and protoxins. This speculation is supported by previous reports from other groups [ 9 , 35 39 ] as well as ours [ 16 , 17 , 40 ] that increased CYP2E1 activity is closely associated with oxidative stress, inflammation, and inflammation-related diseases like nonalcoholic steatohepatitis (NASH), hepatofibrosis, HCC, ovarian cancer, and so on.…”
Section: Discussionsupporting
confidence: 86%
“…This affects the activities of CYPs including CYP2E1, and the important role of CYP2E1 in the activation of procarcinogens and protoxins. This speculation is supported by previous reports from other groups [ 9 , 35 39 ] as well as ours [ 16 , 17 , 40 ] that increased CYP2E1 activity is closely associated with oxidative stress, inflammation, and inflammation-related diseases like nonalcoholic steatohepatitis (NASH), hepatofibrosis, HCC, ovarian cancer, and so on.…”
Section: Discussionsupporting
confidence: 86%
“…To study the relationship between the inhibition of CYP2E1 activity at the hepatofibrosis stage and hepatocarcinogenesis, eight hepatocarcinogenesis model rats received chlormethiazole (CMZ, TCI (Shanghai) Development Co., Ltd.), a CYP2E1 inhibitor, by intraperitoneal injection at 100 mg/kg, 12 hepatocarcinogenesis model rats received an equal volume of saline by intraperitoneal injection and served as a control group. When DEN (50 mg/kg) was given together with CMZ or saline, DEN was administered immediately after the injection of saline or CMZ.…”
Section: Methodsmentioning
confidence: 99%
“…By comparing the physiological and pathological activity of CYP2E1, we previously found that CYP2E1‐mediated probe clearance increased remarkably in hepatofibrotic tissue and positively correlated with enzyme velocity for DEN metabolism. CYP2E1‐mediated probe drug clearance showed intraindividual variation in patients with hepatofibrosis, and the difference in the metabolism of DEN by CYP2E1 may be the cause of hepatofibrosis . Herein CYP2E1 activity was determined by measuring the enzyme velocity for DEN metabolism in human hepatofibrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Herein CYP2E1 activity was determined by measuring the enzyme velocity for DEN metabolism in human hepatofibrotic tissue. We explored the role of CYP2E1 in hepatofibrosis in DEN‐induced rats, which leads to typical liver fibrosis and resembles human hepatofibrosis progression. Our results indicate that the CYP2E1 activity increased in hepatofibrotic tissue adjacent to HCC and had a broad and powerful profibrotic effect in DEN‐treated rats, which was ameliorated by the CYP2E1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation